Investigating Dried Distiller's Grains with Solubles vulnerability to Tribolium castaneum (Herbst) infestation by using choice and no-choice experiments. (March 2016) - Fardisi, Mahsa; Mason, Linda J.; Ileleji, Klein E.; Richmond, Douglas S.
Abstract: Demand for Dried Distiller's Grains with Solubles (DDGS) in international markets and the United States has increased during the past few years. Knowledge of DDGS supplemented animal feed vulnerability to insect infestation is critical for safe feed storage. To assess this vulnerability, it is necessary to know how DDGS is susceptible to insect infestation, while stored as raw ingredient. This research focused on the susceptibility of different types of DDGS (raw and ground) to red flour beetle, T. castaneum, infestation under 30% and 50% relative humidity (r.h.) regimes. Larval period at 30% r.h. increased 2–3 fold on raw DDGS diets with larger particle sizes (PSs) compared with their normal laboratory diet, a mixture of flour and yeast (9:1) (F/Y). However, grinding DDGS samples and increasing the r.h. to 50% decreased the amount of time required for insect development thus increasing DDGS vulnerability to T. castaneum infestation compared with raw DDGS at r.h. of 30%. As was expected, T. castaneum egg and pupal development were not affected by diet or humidity. The results suggested that DDGS as a raw ingredient at 30% r.h. was not a suitable food source for T. castaneum and given a choice, the majority of T. castaneum adults prefer laboratory diet over DDGS. Additionally, fecundity was significantly lower on DDGS compared with the control diets (F/Y and ground corn (GCORN)). These results indicated that these types of DDGS were not suitable developmental diets compared with the F/Y diet if stored at 30% r.h. with larger PSs. Highlights: Tribolium castaneum development was affected by diet and storage r.h. DDGS susceptibility to T. castaneum infestation is minimal at r.h. of 30%. T. castaneum grow faster when fed on ground DDGS at r.h. of 50%. T. castaneum fecundity was lower on DDGS compared with their control diet.